A novel framework for the potential assessment of utility-scale photovoltaic solar energy, application to eastern Iran. (1st November 2017) - Hafeznia, Hamed; Yousefi, Hossein; Razi Astaraei, Fatemeh
Graphical abstract: Highlights: This study assessed the utility-scale photovoltaic solar energy potential. The framework of this study incorporates spatial planning and simulation. The spatial model consists of environmental, socio-economic, technical criteria. The spatial model conducted in GIS environment using Boolean and fuzzy method. The estimated energy output of photovoltaic power plants was simulated by PVsyst. Abstract: This paper presents a framework to assess the potential of photovoltaic solar energy for utility-scale installations. In order to achieve this purpose, the framework incorporates spatial planning and performance simulation of photovoltaic power systems into the potential assessment process. Birjand County where is a suitable region for the deployment of photovoltaic technologies because of its climatic conditions was selected as a case study. The installation of solar power plants as a subset of infrastructure facilities should have the conformity to the standards of land-use planning. At the first step, the set of factors (27 criteria) influencing on the site selection of photovoltaic power plants was defined. After the detection of unsuitable areas, they were excluded from the county map by Boolean logic. Remaining areas were rated based on the technical, socio-economic, environmental criteria by using different fuzzy membership functions. Then, these rated areas were mapped. To determine the optimal sites for the grid-connected installations of photovoltaic, the fuzzified maps were overlaid by fuzzy gamma operator. Then, the pixels of final map were classified into five groups regarding to their fuzzy value. The results show that optimal places for the installation of photovoltaic power plants account for 0.5 percent (2005 hectares) of Birjand's territory. The results of geo-spatial modeling of this thesis were verified by using satellite images. To estimate the capacity of electricity production from photovoltaic power plants, a 46.2 kW- photovoltaic installation was designed and its performance and energy output was simulated under climatic and geographical conditions of Birjand. The estimated energy output of photovoltaic power plants in optimal sites of Birjand County (1781.6 GW h/year) not only can supply the electrical demand of Southern Khorasan Province but also, the excess generated electricity can export to other provinces and neighboring countries such as Pakistan and Afghanistan.